IFITM3 requires an amphipathic helix for antiviral activity. (23rd August 2017) - Chesarino, Nicholas M; Compton, Alex A; McMichael, Temet M; Kenney, Adam D; Zhang, Lizhi; Soewarna, Victoria; Davis, Matthew; Schwartz, Olivier; Yount, Jacob S
Abstract: Interferon‐induced transmembrane protein 3 (IFITM3) is a cellular factor that blocks virus fusion with cell membranes. IFITM3 has been suggested to alter membrane curvature and fluidity, though its exact mechanism of action is unclear. Using a bioinformatic approach, we predict IFITM3 secondary structures and identify a highly conserved, short amphipathic helix within a hydrophobic region of IFITM3 previously thought to be a transmembrane domain. Consistent with the known ability of amphipathic helices to alter membrane properties, we show that this helix and its amphipathicity are required for the IFITM3‐dependent inhibition of influenza virus, Zika virus, vesicular stomatitis virus, Ebola virus, and human immunodeficiency virus infections. The homologous amphipathic helix within IFITM1 is also required for the inhibition of infection, indicating that IFITM proteins possess a conserved mechanism of antiviral action. We further demonstrate that the amphipathic helix of IFITM3 is required to block influenza virus hemagglutinin‐mediated membrane fusion. Overall, our results provide evidence that IFITM proteins utilize an amphipathic helix for inhibiting virus fusion. Synopsis: Interferon‐induced transmembrane protein 3 (IFITM3) is a cellular factor that blocks virus fusion with cell membranes. This study discovers an amphipathic helix within IFITM3 that is required for its inhibition of infection by diverse pathogenic viruses. The amino acids 59–68 of IFITM3 constitute an amphipathic helix. The amphipathic helix IFITM3 is essential for blocking virus infection, e.g. by influenza A virus, vesicular stomatitis virus and Zika virus. The IFITM3 amphipathic helix is essential for blocking virus‐mediated membrane fusion. Abstract : Interferon‐induced transmembrane protein 3 (IFITM3) is a cellular factor that blocks virus fusion with cell membranes. This study discovers an amphipathic helix within IFITM3 that is required for its inhibition of infection by diverse pathogenic viruses.